Enrichment and Characterisation of a Mixed-Source Ethanologenic Community Degrading the Organic Fraction of Municipal Solid Waste Under Minimal Environmental Control - Carrillo-Barragan, Priscilla; Bowler, Bernard; Dolfing, Jan; Sallis, Paul; Gray, Neil Duncan (Frontiers in Microbiology, 2019)
The utilisation of the organic fraction of municipal solid waste as feedstock for bioethanol production could reduce the need for disposal of the ever-increasing amounts of municipal solid waste, especially in developing countries, and fits with the integrated goals of climate change mitigation and transport energy security. Mixed culture fermentation represents a suitable approach to handle the complexity and variability of such waste, avoiding expensive and vulnerable closed-control operational conditions. It is widely accepted that the control of pH in these systems can direct the fermentation process towards a desired fermentation product, however, little empirical evidence has been provided in respect of lignocellulosic waste substrates and different environmental inocula sources. We evaluated ethanol production from the organic fraction of municipal solid waste using five different inocula sources where lignocellulose degradation putatively occurs, namely, compost, woodland soil, rumen, cow faeces and anaerobic granular sludge, when incubated in batch microcosms at either initially neutral or acidic pH and under initially aerobic or anaerobic conditions. Although ethanol was produced by all the inocula tested, their performance was different in response to the imposed experimental conditions. Rumen and anaerobic granular sludge produced significantly the highest ethanol concentrations (~30mM) under initially neutral and acidic pH, respectively. A mixed-source community formed by mixing rumen and sludge (R+S) was then tested over a range of initial pH. In contrast to the differences observed for the individual inocula, the maximal ethanol production of the mixed community was not significantly different at initial pH of 5.5 and 7. Consistent with this broader functionality, the microbial community analyses confirmed the R+S community enriched comprised bacterial taxa representative of both original inocula. It was demonstrated that the interaction of initial pH and inocula source dictated ethanologenic activity from the organic fraction of municipal solid waste. Furthermore, the ethanologenic mixed-source community enriched, was comprised of taxa belonging to the two original inocula sources (rumen and sludge) and had a broader functionality. This information is relevant when diverse inocula sources are combined for mix culture fermentation studies as it experimentally demonstrates the benefits of diversity and function assembled from different inocula.